Liposomal Delivery of Mycophenolic Acid With Quercetin for Improved Breast Cancer Therapy in SD Rats - Patel, Gopal; Thakur, Neeraj Singh; Kushwah, Varun; Patil, Mahesh D.; Nile, Shivraj Hariram; Jain, Sanyog; Banerjee, Uttam Chand; Kai, Guoyin (Frontiers in Bioengineering and Biotechnology, 2020)
The present study explores the influence of mycophenolic acid (MPA) in combination therapy with quercetin (QC) (impeding MPA metabolic rate) and their encapsulation within liposome nanoparticles (LNP). Mycophenolic acid liposome nanoparticle (MPA-LNP) and quercetin liposome nanoparticle (QC-LNP) were individually prepared and comprehensively characterized. The size of prepared MPA-LNP and QC-LNP were found to be 183.40 ± 12.62 and 156.93. ± 09.78 respectively. The in-vitro studies revealed the higher cellular uptake and cytotoxicity of combined therapy (MPA-LNP + QC-LNP) compared to individual one. Moreover pharmacokinetics studies in female SD-rat shown higher T1/2 value (1.94 fold) of combine therapy compared to MPA. Furthermore in animal experiments the anticancer activity was also significantly higher related to other treatments group. The combination therapy of liposomes revealed the new therapeutic approach for the treatment of breast cancer.